Pembentukan Graf Berdasarkan Benda Langit (Bintang) dengan Selisih Nilai MagnitudeTertentu di OIF UMSU - Zulfi Amri; Rizkiyan Hadi (University of Muhammadiyah Sumatera Utara, 2020)
A graph is a representation of a state that can be defined as an ordered set consisting of vertices and arcs. A graph can be formed based on the representation of the relationship of objects by declaring objects as vertices and relationships between objects as arcs. If the celestial body is connected with certain rules, then the celestial body can be formed a graph.The relationship of celestial bodies to each other in this paper is determined by the difference in the level of light (Mv) read magnitude. Difference Mv this paper i.e: , , dan .The purpose of this research is to form a new graph based on luminous celestial bodies (stars).This type of research is field research (field research) with descriptive qualitative approach type, the object used in the study is a star.First determine the amount of light levels of celestial bodies conducted on observations on 9 and 11 July 2019 at OIF UMSU using certain tools along with IRIS software.After the observations are obtained, a connectedness analysis is performed based on the difference in certain magnitudes so that certain graphs based on celestial bodies are obtained.Keywords : Graph, Celestial Bodies, Pseudo Magnitude